Deformation model and experimental evaluation of a contractable and bendable wire-pulling mechanism with embedded soft tubes for a robotic tongue - Nobutsuna Endo (ROBOMECH Journal, 2021)
Abstract Few physical models of oral and laryngeal systems for human speech movement exist for computer or mechanical simulators. In particular, a robot tongue mechanism that fully reproduces the deformation motion of the human tongue is lacking. The human tongue is an aggregate of muscles that is devoid of a skeleton. It possesses only a small hyoid. A mechanism that can drive and control the deformation of a soft body, such as the human tongue, along multiple degrees of freedom has not been realized to date. To solve this problem, a wire-pulling mechanism with embedded soft tubes is proposed. Using this mechanism, a flexible tongue that can be deformed along multiple degrees of freedom without breaking the wire is achieved. A prototype planar mechanism with two degrees of freedom that is capable of contraction and bending was fabricated. A deformation model that assumes a piecewise constant curvature (PCC) was formulated. Deformation tests confirmed that the prototype is capable of contraction and bending movements that are consistent with those of the model. Variations in the error with respect to the hardness of the deformable part are discussed, and the limits of the deformation model based on the PCC assumption are presented.